Exploring the impact of sleep on emotional and physical well-being in professional cricketers: a cohort study over an in-season training period - Grewal, S.; Theijse, R. T.; Dunlop, G.; van Deurzen, D. F. P.; van den Bekerom, M. P. J.; Klautz, R. M. J.; Lefebvre, R. P.; Munsami, D.; Grewal, N. (Frontiers in Sports and Active Living, 2024)
Background: Professional athletes navigate a multitude of unique challenges associated to sport-specific factors (e.g., training, travel and competition) and non-sport factors (e.g., performance pressure, stress and anxiety) that can interfere with healthy sleep behaviors. Sleep plays a key role in proper biopsychosocial development as well as short- and long-term biological, physical, psychological, and cognitive health. As poor sleep quality is known to impair proper brain function, this study aimed to investigate the effect of sleep quality on a professional athlete's ability to train, recover, and perform, as well as their overall emotional and physical well-being.